IoT-Based LPG Gas Leak Monitoring System with Automatic Alarms - Muhammad Hafizal; Safwandi Safwandi; Kurniawati Kurniawati; Muchlis Abd Muthalib; Said Fadlan Anshari (Universitas Islam Indragiri, 2026)
Liquefied Petroleum Gas (LPG) leaks are one of the leading causes of fires in households and LPG distribution facilities. Limited public awareness and delays in detecting gas leaks can significantly increase the risk of property damage and endanger human safety. Therefore, this study aims to design and develop an Internet of Things (IoT)-based monitoring system for 3 kg LPG gas leaks that provides automatic, real-time early warning notifications. The proposed system employs an MQ-2 gas sensor to detect LPG concentration, a NodeMCU ESP8266 as the main controller and data communication module, and a buzzer, LED, and LCD as local warning indicators. A threshold-based method is implemented to classify safe and hazardous conditions according to predefined gas concentration limits. In addition, the system is integrated with remote notifications via Telegram, enabling users to receive alerts even when they are away from the monitored location. Experimental results demonstrate that the proposed system can accurately detect LPG gas leaks under various operating conditions and automatically send warning notifications whenever the gas concentration exceeds the predefined threshold. These findings indicate that the system is effective, responsive, and has strong potential to enhance user safety in the use of LPG.